Nanoparticles laden in situ gel for sustained ocular drug delivery - Himanshu Gupta; Mohammed Aqil; Roop K Khar; Asgar Ali; Aseem Bhatnagar; Gaurav Mittal (Wolters Kluwer Medknow Publications, 2013)
Proper availability of drug on to corneal surface is a challenging task. However, due to ocular physiological barriers, conventional eye drops display poor ocular bioavailability of drugs (< 1%). To improve precorneal residence time and ocular penetration, earlier our group developed and evaluated in situ gel and nanoparticles for ocular delivery. In interest to evaluate the combined effect of in situ gel and nanoparticles on ocular retention, we combined them. We are the first to term this combination as "nanoparticle laden in situ gel", that is, poly lactic co glycolic acid nanoparticle incorporated in chitosan in situ gel for sparfloxacin ophthalmic delivery. The formulation was tested for various physicochemical properties. It showed gelation pH near pH 7.2. The observation of acquired gamma camera images showed good retention over the entire precorneal area for sparfloxacin nanoparticle laden in situ gel (SNG) as compared to marketed formulation. SNG formulation cleared at a very slow rate and remained at corneal surface for longer duration as no radioactivity was observed in systemic circulation. The developed formulation was found to be better in combination and can go up to the clinical evaluation and application.